A sulfur(vi) fluoride exchange click chemistry approach towards main chain liquid crystal polymers bearing sulfate ester groups. Issue 26 (4th June 2019) - Wang, Meng; Jin, Hong-Sheng; Chen, Xu-Man; Lin, Bao-Ping; Yang, Hong
Abstract : Here we report a sulfur(vi ) fluoride exchange click chemistry approach towards the synthesis of main chain liquid crystal polymers. Abstract : In recent years, click chemistry has drawn intense research attention for the fabrication of main-chain liquid crystal polymers (MCLCPs) because of its vast technical advantages, such as ease of operation, green processes, atomic economy and high reaction yields. However, current click chemistry approaches (thiol–ene, thiol–yne and azide–alkyne polyadditions) and all other previous polycondensation methods have to prepare liquid crystal (LC) monomers first and then link LC monomers together to give the designed MCLCPs, efficient synthesis and rapid screening of novel MCLCP materials are still challenging. In this manuscript, a series of fluorosulfate-functionalized monomers and aryl silyl ether-containing monomers are polymerized via the newly-emerged sulfur(vi ) fluoride exchange (SuFEx) click chemistry reaction, to form four MCLCPsP1, P2, P3 andP4, bearing sulfate ester groups in the polymer backbones. The chemical structures of these monomers and MCLCPs are confirmed by GPC and NMR techniques. The combination of DSC, POM and WAXS data indicates that although most of the monomers lack liquid crystallinity, their corresponding MCLCPs all exhibit LC phases.P1 andP3 have a nematic phase with a smectic fluctuation, whileP2 andP4 show a nematic phase. Compared with all the previous polycondensation routes which must synthesize mesogenic monomers first and then prepare the corresponding MCLCPs, this novel SuFEx click chemistry strategy can synthesize MCLCP products from two orthogonal non-LC monomer groups, which might provide a new perspective for efficient synthesis and rapid screening of novel MCLCP materials.